PENGARUH RELIGIUSITAS, HARGA DAN KEMUDAHAN TERHADAP MINAT PENGGUNAAN E-MONEY PADA TRANSPORTASI ONLINE - Nasution, Athirah; Diena Fadhilah; Marpaung, Muslim (Politeknik Negeri Medan, 2020)
This study aims to determine the effect of religiosity, price and convenience partially and simultaneously which have a significant effect on student interest in using e-money. The type of qualitative data, the data sources used are primary data and secondary data. The primary data source was obtained through distributing questionnaires to 100 Muslim students of Medan State Polytechnic obtained by random sampling technique. The method used is descriptive statistics. The data collection technique used a questionnaire which was assessed with ascale Likert and tested for validity and reliability. Prerequisite tests include multicollinearity test, autocorrelation test, heteroscedasticity test. The data analysis technique to answer the hypothesis used multiple linear regression analysis using the SPSS 25 application program. The results obtained showed that religiosity and price partially had a positive and significant effect on student interest in using e-money. Convenience partially does not significantly influence student interest in using e-money. Religiosity, price and convenience simultaneously have a significant effect on student interest in using e-money.